How students' voice can be heard in the Finnish context : the case of primary, lower secondary and upper secondary schools in Jyväskylä - Shatilova, Irina (2014)
This qualitative multiple case study research investigated how the Finnish school system practices student leadership as a significant dimension of democracy on three school levels: primary, lower secondary and upper secondary. The study defines student leadership through the democracy issue, leadership decision making and leadership theories. Semi-structured interviews were applied to collect the data from three school principals, eight teacher supervisors and three groups of student leaders, altogether 33 participants.